BIOLOGICAL CONTROL OF Spodoptera frugiperda (J.E SMITH) (LEPIDOPTERA: NOCTUIDAE) GLOBALLY AND NEWLY NATURAL ENEMY ASSOCIATIONS IN ASIAN COUNTRIES: A REVIEW - ASIRI SINGHAMUNI; Azidah Abdul Aziz (Journal of Animal and Plant Sciences, 2026)
Spodoptera frugiperda (J.E Smith) is a destructive pest of maize (Zea mays L.) around the globe. It originated from the American continent and subsequently invaded Africa and Asia. Despite its recent invasion into Asia, some countries such as India, China, Pakistan, the Philippines, Indonesia, Sri Lanka, Malaysia, and Nepal have already reported numerous bio-control agents of S. frugiperda. In Asia, several bio-control agents of S. frugiperda are frequently encountered, including the egg parasitoid, Telenomus remus (Nixon) and the egg-larval parasitoid, Chelonus formosanus (Sonan). The Hymenopteran family Braconidae was the presiding larval parasitoid group, while the dominant predatory groups belong to family Reduviidae, Coccinellidae, and Pentatomidae. T. remus is considered the most effective and extensively used bio-control agent of S. frugiperda. Therefore, we discuss the potential of the bio-control agents and successful efforts in the biological control programme globally, along with new natural enemy associations with recently invaded S. frugiperda in Asian countries. This review may encourage other Asian nations with S. frugiperda problem to adopt natural enemies-based sustainable and environmentally friendly approaches.
Keywords: Asia; bio-control; natural enemies; parasitoids; predators; Spodoptera frugiperda